2007
DOI: 10.1562/0031-8655(2002)0750272accipl2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Carotenoid Content in Plant Leaves with Reflectance Spectroscopy¶

Abstract: Spectral reflectance of maple, chestnut and beech leaves in a wide range of pigment content and composition was investigated to devise a nondestructive technique for total carotenoid (Car) content estimation in higher plant leaves. Reciprocal reflectance in the range 510 to 550 nm was found to be closely related to the total pigment content in leaves. The sensitivity of reciprocal reflectance to Car content was maximal in a spectral range around 510 nm; however, chlorophylls (Chl) also affect reflectance in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 33 publications
(89 reference statements)
2
92
1
3
Order By: Relevance
“…Norway maple and horse chestnut leaves were from a park at Moscow State University (Russia), beech leaves were from the University of Karlsruhe campus (Germany). The leaf total Chl and Car content was determined analytically from the same leaf samples used for reflectance measurement (details are in Gitelson et al, 2001Gitelson et al, , 2002Gitelson et al, , 2003. Pigment content was expressed on a leaf area basis.…”
Section: Pigment Content and Reflectance Measurementmentioning
confidence: 99%
“…Norway maple and horse chestnut leaves were from a park at Moscow State University (Russia), beech leaves were from the University of Karlsruhe campus (Germany). The leaf total Chl and Car content was determined analytically from the same leaf samples used for reflectance measurement (details are in Gitelson et al, 2001Gitelson et al, , 2002Gitelson et al, , 2003. Pigment content was expressed on a leaf area basis.…”
Section: Pigment Content and Reflectance Measurementmentioning
confidence: 99%
“…The former band is located within a section of the vegetation spectral curve known as the green edge, i.e. the reflectance increase from the strong absorption of blue region to the reflection peak in the green region (between 480 and 530 nm), which is maximally sensitive to the bulk foliar pigment content (Gitelson et al, 2001(Gitelson et al, , 2002b. NIR wavelengths, by contrast, are well-known for their sensitivity to changes in foliage amount.…”
Section: Spectral and Biophysical Interpretationmentioning
confidence: 99%
“…To build upon previous work, we determined the genetic variation across source populations in the concentrations of pigments, F PSII and ETR in relation to the variation in SLA and N. We also sought linkages between leaf biochemical and physiological characteristics and their spectral reflectance and absorption properties, the latter being two integrative measures of overall leaf functional status. Previous work has shown that the amount and quality of visible light reflected from leaves is linked to leaf structure, N and pigment concentrations (Gates et al 1965;Curran 1989); indices derived from narrowband reflectance and transmittance are often correlated with foliar concentrations of N and Chl (Markwell et al 1995;Richardson et al 2002;Sims and Gamon 2002;Gitelson et al 2003;le Maire et al 2004), Car (including specific xanthophyll pigments) and anthocynanin, as well as with the light-use efficiency of photosynthetic carbon gain (Gitelson et al 2001(Gitelson et al , 2002Merzlyak et al 2003). Our study thus included leaf reflectance and absorption measurements to evaluate if spectral patterns of light use correlate with leaf biochemical constituents in a way that is indicative of photosynthetic capacity across distinct phenotypes of M. polymorpha.…”
Section: Introductionmentioning
confidence: 99%